INCREASE STUDENT ACTIVITY IN MATHEMATICS USING COOPERATIVE LEARNING MODEL TYPE OF THINK PAIR SQUARE (TPS) - Istin Fauziah; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The research was conducted because of low student activity in learning mathematics. The purpose of this research is to improve the activity of students in learning mathematics using the cooperative learning model of think pair square (TPS) in class VII of even semester at SMP Muhammadiyah 2 Prambanan. This research was conducted at SMP Muhammadiyah 2 Prambanan. The type of research is classroom action research. Subjects of this research were students of class VII of even semester at SMP Muhammadiyah 2 Prambanan academic year 2015/2016, amounting to 35 students. The object of the research is a cooperative learning model type TPS. Data analysis used qualitative descriptive analysis. The research instruments are student activity observation sheets, teacher activity observation sheets, and interview guides. Success in learning characterized by an increased average percentage of student activity achieved at least a good criteria (â‰¥ 61 %). Â The result of this research indicates that the use of mathematical models of cooperative learning type of TPS can enhance student activity. From the observation sheet, there was an increase in student activity with the student in learning mathematics using TPS. In the first cycle, the average student activity reached 57,857% with enough criteria, and the second cycle increased to 64,584% with good criteria. From interview showed a positive response from students to use cooperative learning model type TPS.